"A Gift We Are Unable to Create Ourselves": Uncertainty Reduction in Online Classified Ads Posted by Gay Men Pursuing Surrogacy. Issue 5 (19th October 2016) - May, Amy; Tenzek, Kelly
ABSTRACT: Surrogacy is becoming an increasingly popular way for gay men to start a family. Those choosing surrogacy must navigate intensive medical procedures, complex interpersonal dynamics, legal maneuverings, and a society that views parenting through a heteronormative lens. With so many unknowns, the need to reduce uncertainty is significant. Online communities offer a starting point, providing information, advice, and classified ads for matching with a surrogate. This investigation employs a qualitative framework for understanding how strategic messaging in online ads featured on surromomsonline.com, the website of Surrogate Mothers Online, LLC, reduce uncertainty and facilitate the matching process for gay men. Analysis identified common themes in ads posted by gay intended parents. Uncertainty reduction theory provides a theoretical framework for understanding how these communication strategies function to reduce uncertainty and facilitate the communication process. The results illustrate that for gay intended parents seeking surrogates, strategic messaging is utilized to reduce uncertainty associated with relationship stability and commitment, financial strength, social support from extended networks, and the ability to navigate the legal and logistical concerns associated with surrogacy and parenting. The findings offer new insights into the gay surrogacy journey.